Hubungan Pengetahuan Dengan Sikap Mahasiswa Keperawatan Pada Perawatan Paliatif Menjelang Ajal - Umara, Annisaa Fitrah; Rara Salsa Bilya, Ingee; Latipah, Siti (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
The need for palliative nursing services is very high but has not been met properly. This is due to the lack of knowledge, skills and capacity of health workers in providing palliative care. Palliative nursing courses have only been introduced to nursing students who have received special courses related to Islamic education. The purpose of this study was to determine the relationship between knowledge and attitudes of nursing students towards palliative care for the dying. The cross-sectional method used a purposive sampling technique. A total of 115 nursing students involved had received Palliative Nursing and religious courses. The level of knowledge was measured using the Palliative Care Quiz for Nursing (PCQN) questionnaire and attitudes using the Frommelt's Attitude Toward Care of the Dying (FATCOD) scale questionnaire. The results of the study showed that the majority of knowledge levels of palliative nursing were sufficient and attitudes towards palliative care for the dying were negative. In conclusion, there was no significant relationship between the level of knowledge and attitudes towards palliative care for the dying with p>0.05. It is suggested that nursing students' knowledge needs to be balanced by improving attitudes in palliative care for the dying.